Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) pada Masyarakat Baduy Leuwi Damar Desa Kanekes Lebak, Banten - Siti Nur Ramdaniati; Ega Egriana Handayani; Lambang Satria Himmawan; Dea Maelani; Putri Aulia Jasmine; Ahmad Solihin; Miki Septa Ferdinan; Ahmad Nizar Subakti (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2026)
Clean and Healthy Living Behavior (PHBS) is a promotive and preventive effort aimed at improving the level of public health. The Baduy indigenous community in Leuwi Damar, Kanekes Village, Lebak Regency, Banten Province has local wisdom and traditional lifestyles that influence daily health practices. However, limited access to information and health services is a challenge in implementing PHBS optimally. This article aims to describe the implementation of PHBS education in the Baduy Leuwi Damar community and its impact on community knowledge and attitudes. The method used is a descriptive approach with educational activities through counseling, discussion and simple demonstrations adapted to local culture. Educational material includes personal hygiene, clean water management, environmental sanitation, and healthy living behavior in daily life. The results of the activity showed an increase in public understanding regarding the importance of personal and environmental hygiene, as well as the emergence of a positive attitude towards implementing PHBS without eliminating the traditional values adhered to. PHBS education carried out using a simple cultural and communication approach is considered effective in increasing the health awareness of the Baduy community. Therefore, health education programs based on local wisdom need to continue to be developed as a strategy to improve the health of indigenous communities. .(Riset Kesehatan Dasar,2019).